SEED GERMINATION OF ALEPIDEA SPECIES – HEAVILY TRADED AND THREATENED MEDICINAL PLANTS IN SOUTH AFRICA - Mulaudzi, R.; Kulkarni, M.; Finnie, J.; Van Staden, J. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The rhizomes of A. amatymbica are widely used as a remedy for cold, cough, asthma, influenza, diarrhoea and abdominal cramp. Due to the scarcity and increasing demand for this species, the rhizomes of Alepidea natalensis are being uprooted as an alternative plant source. As the reproductive biology of both the species is not well defined, conditions and treatments required for optimum germination of these species were studied. Seeds were exposed to various physical factors such as temperature, light conditions, cold stratification and storage. Smoke-water, the newly identified smoke-compound butenolide (3-methyl-2H-furo [2, 3-c] pyran-2-one) and plant growth regulators were also tested. Alepidea amatymbica and A. natalensis achieved the highest seed germination (72% and 80% respectively) at 25 ºC under a 16:8 h light/dark condition with a mean germination time (MGT) of 18 and 12 days respectively. A temperature of 35 °C was detrimental to both species as none of the seeds germinated. Cold stratification (5ºC) significantly improved the percentage germination of both species (> 90%) compared to non-stratified (control) at 25 ºC under a 16:8 h light/dark regime. Five months storage of A. natalensis seeds at room temperature (25±2ºC) showed maximum germination (99%) with a MGT of 9 days. Smoke-water-treated seeds of A. amatymbica significantly enhanced germination from 72 to 91%. Plant growth regulators were less effective in increasing the germination of both the species. Findings of this study can be used to propagate these medicinal species to meet the current demand. Acknowledgements: Canon Collins Trust and NRF